2015
DOI: 10.7150/ijms.12446
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and Risk of Hypertension: Follow-Up of a Young Pre-Hypertensive Cohort

Abstract: Objectives: To determine whether healthy lifestyle decreases the risk of developing hypertension in pre-hypertensive patients.Study design: A longitudinal study.Setting & participants: Randomly selected pre-hypertensive young adults 20-45 years old without any vascular disease such as stroke or diabetes.Predictors: Four lifestyle factors (a body mass index [BMI] of 18.5-24.9 kg/m2, regular physical activity, no alcohol use and 6-8 h of sleep per day), individually and in combination.Outcomes: Hypertension was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 28 publications
(26 reference statements)
3
36
0
4
Order By: Relevance
“…In China, there has been a steady increase in the prevalence of hypertension during the past decade. Interestingly the increasing trend of hypertension prevalence varies across different populations 12-18. That trend induces researchers' interests and effort in investigating possible risk factors of hypertension, and in turn analyzing the risk factors of cardiovascular diseases as hypertension's comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In China, there has been a steady increase in the prevalence of hypertension during the past decade. Interestingly the increasing trend of hypertension prevalence varies across different populations 12-18. That trend induces researchers' interests and effort in investigating possible risk factors of hypertension, and in turn analyzing the risk factors of cardiovascular diseases as hypertension's comorbidities.…”
Section: Introductionmentioning
confidence: 99%
“…In a study, compared with a BMI of 18.5-24.9 kg/m 2 , a BMI of 25-30 kg/m 2 and a BMI of >30 kg/m 2 were associated with an increased risk of hypertension occurrence. [24] In the present study, the urinary creatinine level was found to be significantly (p=0.018) higher among the study group (1.37±0.86) compared to controls (1.00±0.38). Hasit et al [25] observed that the urinary albumin creatinine ratio was lesser than the established microalbuminuric range of 30-300 mg/g, in both study and controls irrespective of the values obtained for lipid profile and anthropometric indices.…”
Section: Discussionmentioning
confidence: 55%
“…These factors were studied that they were associated with the success of goal attainments in CVD risk factors. [29][30][31][32][33] The different categories of healthcare coverage were not associated with the achievement for controlling CVD risk factors. It is implied that the patients do not have problems for the accessibility to health services and the quality of health services among these healthcare coverages are equal.…”
Section: Discussionmentioning
confidence: 90%
“…The multivariate analysis showed that the associated factors for patients to achieved target LDL‐C level < 70 mg/dL were patients with age > 65 years while the patients who were less likely to achieve target BP and HbA1C were patients having BMI ≥23 kg/m 2 and patients with duration of diabetes more than 10 years. These factors were studied that they were associated with the success of goal attainments in CVD risk factors …”
Section: Discussionmentioning
confidence: 99%